Dual role for Sox2 in specification of sensory competence and regulation of Atoh1 function. Issue 1 (6th June 2016) - Puligilla, Chandrakala; Kelley, Matthew W.
ABSTRACT: The formation of inner ear sensory epithelia is believed to occur in two steps, initial specification of sensory competent (prosensory) regions followed by determination of specific cell‐types, such as hair cells (HCs) and supporting cells. However, studies in which the HC determination factor Atoh1 was ectopically expressed in nonprosensory regions indicated that expression of Atoh1 alone is sufficient to induce HC formation suggesting that prosensory formation may not be a prerequisite for HC development. To test this hypothesis, interactions between Sox2 and Atoh1, which are required for prosensory and HC formation respectively, were examined. Forced expression of Atoh1 in nonprosensory cells resulted in transient expression of Sox2 prior to HC formation, suggesting that expression of Sox2 is required for formation of ectopic HCs. Moreover, Atoh1 overexpression failed to induce HC formation in Sox2 mutants, confirming that Sox2 is required for prosensory competence. To determine whether expression of Sox2 alone is sufficient to induce prosensory identity, Sox2 was transiently activated in a manner that mimicked endogenous expression. Following transient Sox2 activation, nonprosensory cells developed as HCs, a result that was never observed in response to persistent expression of Sox2. These results, suggest a dual role for Sox2 in inner ear formation. Initially, Sox2 is required to specify prosensory competence, but subsequent down‐regulation of Sox2 must occur to allow Atoh1 expression, most likely through a direct interaction with the Atoh1 promoter. These results implicate Sox2‐mediated changes in prosensory cells as an essential step in their ability to develop as HCs. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 3–13, 2017